Potential microbiological contamination of effluents in poultry and swine abattoirs - Barros, L. S. S.; Amaral, L. A.; Lorenzon, C. S.; Junior, J. L.; Machado Neto, J. G. (Cambridge University Press, 2007)
Health risks in the effluents of seven swine abattoirs and of seven poultry abattoirs were evaluated with regard to environment degradation and to dissemination of pathogenic microorganisms during the rainy and dry seasons. Supply-water samples from affluents and effluents of the treatment systems at different sites within the abattoir processing system were analysed. Similarly, water samples from the three recipient sites (emission point, 100 m upstream, 100 m downstream) were also analysed. Temperature, free residual chlorine (FRC), total coliform bacteria, Escherichia coli, enterococci, identification and serotyping of salmonellae were assessed. Scalding is the most significant stage in the slaughtering chain (P<0.05) when temperature is taken into account. Temperatures Lit effluents and at the sampled sites in the water bodies accorded to state and federal legislation standards. Supply waters did not meet the standards for FRC and microbial count standards according to the Ministry of Health and within limits imposed by the Industrial and Sanitary Inspection Regulations for Animal Products. Feather plucking and evisceration in Poultry slaughter and the cleansing of carcasses and facilities in Poultry and swine slaughtering had the highest contamination impact. The three loci at the water bodies were above the microbiological standards for classes II and III sites, in conformity with Law 8468 of the state of São Paulo, Brazil and Conama. Salmonella was found at several sites during slaughter, at both types of abattoirs, including in the effluent treatment system. This showed that these sites were the dissemination sources of the microorganism.